The governance of regional networks in the process of European integration - Riccardo Cappellin (European Regional Science Association (ERSA), 2001)
The paper illustrates the model of territorial networks and it investigates the role of institutions in a bottom-up approach of economic and institutional integration aiming to tackle the negative impacts of the globalization process on the economic development. The first chapter illustrates in analytical terms the model of territorial networks and the multidimen-sional nature of the process of integration, in a regional and international setting and it contrasts it with the traditional neoclassical model of price competition and of aggregate efficiency. The second chapter illustrates the concept of organizational/institutional distance and it analyses the various forms of interregional interdependence between developed and less developed regions and it contrasts them with the neoclassical model of market integration and interregional competition. The third chapter investigates the impact of the European Union enlargement on a reform of the aims and instruments of EU regional policy and the characteristics of a regional policy appropriate to the aim of the integration of the new accessing countries in the European Union. Finally, the fourth chapter illustrates the role of institutions in the governance of the international economic relations and the lessons which may be derived from the process of European integration in order to tackle the impact of the globalization process on less developed countries. Key words: Globalization, European Integration, networks, distance, institutions Prof. Riccardo Cappellin
Keywords: 330